Comparing productivity of rice under system of rice intensification and conventional flooding: A switching regression approach - Kaloi, Francis Kadipo; Isaboke, Hezron N.; Onyari, Charles N.; Njeru, Lucy K. (Academic Journals, 2020)
This paper examined the factors influencing rice productivity in Mwea Irrigation Scheme using the System of rice intensification (SRI) and conventional flooding (CF). Stratified sampling was used to obtain 364 smallholder rice farmers for interviewing. Data collection was done with the aid of a semistructured questionnaire and analyzed using the Endogenous Switching regression Model (ESRM). The results of ESRM revealed that factors such as household size, access to extension services, involvement in off-farm work, distance from the canal, farm size, labour use, access to credit services and years spent in rice farming were found to be significant in explaining variations in rice productivity. Furthermore, the gross margin analysis showed that the returns of SRI outweigh the returns of CF, thus making SRI more profitable than CF. The study therefore recommends that Kenya government should enhance engagement with development partners to pay attention to all significant factors which are important in making decisions in the two practices of rice production.
Keywords: System of rice intensification (SRI); rice; Mwea irrigation scheme; productivity